Performance improvement of gaseous hydrocarbon fuel driven thermal power generation systems for hypersonic vehicles. (1st November 2019) - Li, Haowei; Qin, Jiang; Bao, Wen; Huang, Hongyan
Highlights: Two TPG improvement methods are brought out. The partial mass flow TPG improvement method is discussed with an analytical model. The catalytic steam reformed hydrocarbon fuel TPG improvement is studied. The two TPG improvement methods are compared. Abstract: Onboard power generation for hypersonic vehicles is an important and urgent requirement. The capability of existing gaseous hydrocarbon fuel driven thermal power generation (TPG) is poor at low Mach speed range. To improve the TPG capability, two potential power generation improvement methods have been proposed in this study, namely: 1) the partial mass flow TPG improvement method and 2) the catalytic steam reformed hydrocarbon fuel TPG improvement method. The characteristics of the two TPG improvement methods are studied using an analytical model. The results show that the former can improve power generation capability with less fuel mass flow and the maximum output power improvement ratio can be as high as 14 at low heat flux condition, while the latter helps to generate power at a much lower fuel temperature, which could be as low as 710 K, although it requires extra water steam. Therefore, both methods are useful and the appropriate method should be selected according to the working conditions of scramjet. If the Mach number is rather low and scramjet cannot take extra water, it is better to use the partial mass flow TPG improvement method. Otherwise, the catalytic steam reformed hydrocarbon fuel TPG improvement method is more suitable.